Effects of Juglone on Neutrophil Degranulation and Myeloperoxidase Activity Related to Equine Laminitis - Mouithys-Mickalad, Ange; Storms, Nazaré; Franck, Thierry; Ceusters, Justine; de la Rebière de Pouyade, Geoffroy; Deby-Dupont, Ginette; Serteyn, Didier (Frontiers in Veterinary Science, 2021)
Experimental laminitis, characterized by a failure of the dermal–epidermal interface of the foot, can be induced in horses by the oral administration of a black walnut extract (BWE). In the early phase of this severe and painful disease, an activation of neutrophil occurs, with the release of myeloperoxidase (MPO), a pro-oxidant enzyme of neutrophils, in plasma, skin, and laminar tissue. Juglone, a naphthoquinone derivative endowed with redox properties, is found in walnuts and has been incriminated in this neutrophil activation. We report for the first time the inhibitory activity of juglone on the degranulation of neutrophils induced by cytochalasin B and formyl-methionyl-leucyl-phenylalanine as monitored by the MPO release (>90% inhibition for 25 and 50 μM). Moreover, it also acts on the peroxidase activity of MPO by interacting with the intermediate “π cation radical,” as evidenced by the classical and specific immunological extraction followed by enzymatic detection (SIEFED) assays. These results are confirmed by a docking study showing the perfect positioning of juglone in the MPO enzyme active site and its interaction with one of the amino acids (Arg-239) of MPO apoprotein. By chemiluminescence and electron paramagnetic resonance techniques, we demonstrated that juglone inhibited reactive oxygen species (ROS) and superoxide anion free radical produced from phorbol myristate acetate (PMA)-activated polymorphonuclear neutrophils (PMNs). These results indicate that juglone is not the trigger for equine laminitis, at least if we focus on the modulation of neutrophil activation.